Governing Blockchain-based Token in Indonesia: Legal and Technical Perspective - Yun Santoso, Wahyu; Anggara Putra, Araya; Hendson Passagi, Jonathan; Rifky Hanindya, Yoda; Azura Tagar, Annisa (Faculty of Law, Universitas Brawijaya, 2020)
In the past decade, blockchain technology has caught the world's attention because of its disruptive nature in various industries. Along with blockchain adoption, blockchain-based token, or more popularly known as the